2021
DOI: 10.37304/jkupr.v9i2.3525
|View full text |Cite
|
Sign up to set email alerts
|

Profil Penderita Dengan Tumor Payudara Yang Dibiopsi Di Rumah Sakit Siloam MRCCC Semanggi Pada Tahun 2017-2018

Abstract: Pendahuluan: Benjolan payudara merupakan jaringan lain yang tumbuh di dalam payudara yang berisikan massa/lemak/cairan, dan merupakan dampak dari perubahan fisiologis tubuh yang dapat berupa tumor jinak, tumor ganas, dan hiperplasia payudara. Namun, Indonesia belum ada data yang lengkap mengenai angka kejadian FAM. Tujuan: Mengetahui bagaimana profil penderita dengan tumor payudara yang dilakukan biopsi di Rumah Sakit Siloam MRCCC Semanggi pada tahun 2017-2018, mengetahui jenis benjolan payudara, dan jumlah tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Meanwhile, a study by the Jakarta Breast Center found 1,971 patients suffering from benign FAM tumors from 2,495 case samples of patients who came for checkups. Meanwhile, from research data at the Siloam MRCCC Semanggi Hospital from 2017 to 2018, the results found 50 out of 304 total patients suffering from FAM aged 20 to 39 years [22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, a study by the Jakarta Breast Center found 1,971 patients suffering from benign FAM tumors from 2,495 case samples of patients who came for checkups. Meanwhile, from research data at the Siloam MRCCC Semanggi Hospital from 2017 to 2018, the results found 50 out of 304 total patients suffering from FAM aged 20 to 39 years [22].…”
Section: Literature Reviewmentioning
confidence: 99%